A new family of the order Ctenopoda (Crustacea: Cladocera) from the depths of the Black Sea - Korovchinsky, Nikolai M.; Sergeeva, Nelli G. (Zootaxa, 2008)
The recently described Pseudopenilia bathyalis Sergeeva, 2004, found in the depths of the Black Sea and initially attributed to family Sididae (Crustacea: Cladocera: Ctenopoda), have after reinvestigation been placed in Pseudopenilidae, a new family of the cladoceran order Ctenopoda. The following set of the main diagnostic features characterize Pseudopenilidae: comparatively large antennules with long sensory seta and five aesthetascs; long and massive second antennae with two-segmented branches armed with long, one-segmented, needle-shaped setae without setules; maxillules without long setae; lack of second maxillae; closed brood pouch; six pairs of similar thoracic limbs without gnathobases and filtering setae; small epipodites present only on thoracic limbs of first pair; large postabdomen, having massive terminal claws and one-segmented, needle-shaped setae nanatoriae without setules; resting eggs with hard outer shell. Among Ctenopoda, Pseudopenilidae is closest to the marine Penilia (family Sididae, subfamily Penilinae) but is at the same time very different. P. bathyalis is a member of the recently discovered community of invertebrates, populating the deep anaerobic zone of the Black Sea, whose taxonomic diversity and mode of existence need further investigations.